The Pronunciation of Egyptian Arabic and Its Aspect of Sociolinguistic - Nanda, Fitra; Astari, Rika; Seman, Haji Mohammad bin (Universitas Islam Negeri Raden Intan Lampung, 2020)
The purpose of this research is to provide insight into the characteristics of the Amiyah Egyptian language from a sociolinguistic point of view. This research was conducted by examining a variety of literature relating to the object of study and also the deepening of the material regarding sociolinguistics itself. The research method used is note taking, which takes data from YouTube consisting of 10 video objects whose results are presented in descriptive form. The procedures of the research are as 1) listening to every phrase which is spoken by the speaker, 2) writing the vocabulary that has phonological differences with Arabic Fusha, 3) classifying data according to sound change prepositions, 4) analyzing data related to phonological and morphological aspects, 5) doing further analysis related to the sociolinguistic point of view, 6) presents the results of the study. The results of this study, Amiyah Arabic is not included as a language but as a dialect that emerges from a basic language, namely Fusha Arabic. However, amiyah language has different phonological and morphological aspects that have become characteristic of being another language. This was explained by the social conditions of the Egyptian community who held that the language variations formed were higher social classes than the existing basic language namely fusha language.